2022
DOI: 10.1371/journal.pone.0277981
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measured LDL cholesterol with calculated LDL-cholesterol using the Friedewald and Martin-Hopkins formulae in diabetic adults at Charlotte Maxeke Johannesburg Academic Hospital/NHLS Laboratory

Abstract: Background The National Cholesterol Education Programme Adult Treatment Panel III (NCEP ATP III) and the European Society of Cardiology recommend using low-density lipoprotein cholesterol (LDL-C) as a treatment target for cholesterol lowering therapy. The Friedewald formula underestimates LDL-C in non-fasted and hypertriglyceridemia patients. This study aimed to compare measured LDL-C to calculated LDL-C in diabetic patients using the Friedewald and Martin-Hopkins formulae. Methods The data of 1 247 adult di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Their analysis found a mean difference of -23.0 mg/dl, with limits of agreement ranging from -72.4 mg/dl to 26.4 mg/dl [17] . Dintshi et al (2022) compared measured LDL-C with calculated values using both the Friedewald and Martin-Hopkins formulae in diabetic adults. Their study revealed a mean positive bias of 14% for the Friedewald formula and 10.24% for the Martin-Hopkins formula, highlighting substantial differences between measured and calculated LDL-C values [18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis found a mean difference of -23.0 mg/dl, with limits of agreement ranging from -72.4 mg/dl to 26.4 mg/dl [17] . Dintshi et al (2022) compared measured LDL-C with calculated values using both the Friedewald and Martin-Hopkins formulae in diabetic adults. Their study revealed a mean positive bias of 14% for the Friedewald formula and 10.24% for the Martin-Hopkins formula, highlighting substantial differences between measured and calculated LDL-C values [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Dintshi et al (2022) compared measured LDL-C with calculated values using both the Friedewald and Martin-Hopkins formulae in diabetic adults. Their study revealed a mean positive bias of 14% for the Friedewald formula and 10.24% for the Martin-Hopkins formula, highlighting substantial differences between measured and calculated LDL-C values [18] . Similarly, Kannan et al (2014) found a strong positive correlation (r = 0.89) between LDL-C calculated using the Friedewald formula and directly measured LDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…A good deal of external validations confirm that Martin/Hopkins equation outperforms others in accuracy. 11 24 26 27 28 29 30 31 32 33 34 35 36 …”
Section: Methodsmentioning
confidence: 99%
“…Many external validation studies have been conducted and showed superiority of the Martin/Hopkins 11 24 26 27 28 29 30 31 32 33 34 35 36 or NIH Equation 2 25 27 37 38 in relation to the Friedewald formula. Here, the purpose of this study was to assess the practical differences 39 40 in LDL-C estimates calculated by Friedewald, Martin/Hopkins, or NIH equation 2 in a population-based, random-sampled, noninstitutionalized general U.S. sample.…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, the equation does not account for interindividual variances in the triglyceride (TG):very-low-density lipoprotein cholesterol (VLDL-C) (TG:VLDL-C) ratio 17 ; it is based on a presumption that this ratio is constantly 5:1, when in fact, it is highly variable through different TG and non-high-density lipoprotein cholesterol (non-HDL-C) levels 14 , 17 ; the Lipid Research Clinics Prevalence Study reported a mean TG:VLDL-C ratio that ranges from 5.2 to 8.9 18 . Therefore, it is invalid at TG levels > 4.5 mmol/L 19 ; particularly observed in diabetes mellitus (DM) and metabolic disorders 20 . Some studies have also questioned its accuracy with TG levels < 4.5 mmol/L and at optimal TG levels (< 0.80 mmol/L) 20 22 .…”
Section: Introductionmentioning
confidence: 99%